A emissão de debêntures e seus reflexos sobre o retorno e o risco das ações de empresas brasileiras - Renata Drumond Pinto Coelho (2008)
This paper aims for analyze possible reflections of issuing debts on the stock return and on the risk of Brazilian companies. If, in one hand, the issuance of debts may signal to the market favorable prospectuses about these companies by increasing leverage and the possibility of funding for new projects, on the other hand, it can signal unfavorable prospectuses by the need to appeal to new external funds, indicating inability to finance through own resources. In order to examine such possible reflections on stock return, the event study methodology was applied to two distinct events: a) the deliberation of debts issuance in the extraordinary general assembly or meeting of the board; and b) the registration of the debts issuance in the brazilian securities commission (CVM). On the risk case, an analysis of variance (ANOVA) was applied in order to verify the possible existence of statistically significant variations in stock systematic risk, measured by beta, after the two specified events. This study was conducted on a sample of 65 issuances of 37 Brazilian companies, listed in Bovespa, which issued bonds between January 2002 and October 2007 and that were part of the IBrX (Index Brazil) in the same period. The empirical evidence showed average cumulative abnormal returns negatives statistically significant in the period near to day zero, only when the event of the registration of the debts issuance in the Brazilian securities commission was considered, pointing to the semi-strong inefficiency of Brazilian market and negative signs for the debts issuance. Concerning the risk, there was no statistically significant variations afterany of the events. Moreover, a model of multiple regression was estimated in order to detect possible explanatory variables for the returns abnormal found. The regression analysis showed that the profitability of the company has statistically significant linear relationship with the abnormal returns.